QR-Learning: la invisiblidad de la mujer en el arte - Moreno Vera, Juan Ramón (2016)
The goal of this study is to promote learning in a very concrete field: the role developed by women in the arts. To reach this goal the use of mobile devices has been integrated in the teaching&learning process in order to improve the results permitting students to use daily tools, improving their knowledge, conducts, abilities and values. The QR codes research has been centered in the topic of gender equality in art history due to its invisibility in history teaching where the students had to research starting from a minimal or non basis. Groups of students has been created to work about women artists in art history and, with the information retrieved, they were asked to create QR codes that will be used as didactic tools for future primary education students. The results of the didactic action were very positive as, when starting the experience, the 99% of the students were uncapable to name any women artist in the age of Renaissance or Baroque; while after researching and creating their QR codes the 97% of the students were capable to name, at least, two women artists of the ages. This relevant change is due to the importance that students give to work about invisible topics as women in art history, to the labour of investigation that permits students to build their own knowledge and, finally, to the fact of working cooperatively in small research groups.